Математическое обоснование периода равновесия системы «хищник» - «жертва» - Никифоров, В. В.; Назарова, Ольга Петровна; Назарова, Ольга Петрівна; Nazarova, Olha (ФОП Однорог Т. В., 2019)
RU: Предложенный метод дает возможность получить условие существования равновесия системы «жертва» - «хищник» с определением периодичности и условий существования для равновесия системы. EN: The article discusses the conditions of existence of the equilibrium of the “victim” - “predator” system with the definition of a constant period for the system to return to its initial state. The proposed method allows you to mathematically justify the period in the struggle of species for existence.
Keywords: равенство; период; идентичность; условия существования; equality; identity; period; attribute; return period; conditions of existence; territory